Malignancy in the Upadacitinib Clinical Trials for Rheumatoid Arthritis, Psoriatic Arthritis, Ankylosing Spondylitis, and Non-radiographic Axial Spondyloarthritis - Andrea Rubbert-Roth; Adriana M. Kakehasi; Tsutomu Takeuchi; Marc Schmalzing; Hannah Palac; Derek Coombs; Jianzhong Liu; Samuel I. Anyanwu; Ralph Lippe; Jeffrey R. Curtis (Rheumatology and Therapy, 2023)
Abstract Introduction This article aims to describe malignancies in patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA), ankylosing spondylitis (AS), or non-radiographic axial spondyloarthritis (nr-axSpA) treated with upadacitinib (UPA) or active comparators. Methods This integrated safety analysis includes data from 11 phase 3 UPA trials across RA (6 trials), PsA (2 trials), AS (2 trials; one phase 2b/3), and nr-axSpA (1 trial). Treatment-emergent adverse events (TEAEs) were summarized for RA (pooled UPA 15 mg [UPA15], pooled UPA 30 mg [UPA30], adalimumab 40 mg [ADA], methotrexate monotherapy [MTX]), PsA (pooled UPA15, pooled UPA30, ADA), AS (pooled UPA15), and nr-axSpA (UPA15). TEAEs were reported as exposure-adjusted event rates (events/100 patient-years). Results Median treatment duration ranged from 1.0 to 4.0 years (with a maximum of 6.6 years in RA). Across treatments and indications, rates of malignancy excluding nonmelanoma skin cancer (NMSC) ranged from 0.2 to 1.1, while NMSC ranged from 0.0 to 1.4. In RA, rates of malignancy excluding NMSC were generally similar between UPA15, UPA30, ADA, and MTX (breast and lung cancer were the most common). In RA and PsA, Kaplan–Meier analyses revealed no differences in event onset of malignancy excluding NMSC with UPA15 versus UPA30 over time. In RA, NMSC rates were higher with UPA30 than UPA15; both UPA15 and UPA30 were higher than ADA and MTX. In PsA, rates of malignancy excluding NMSC and NMSC were generally similar between UPA15, UPA30, and ADA. In AS and nr-axSpA, malignancies were reported infrequently. Few events of lymphoma were reported across the clinical programs. Conclusion Rates of malignancy excluding NMSC were generally similar between UPA15, UPA30, ADA, and MTX and were consistent across RA, PsA, AS, and nr-axSpA. A dose-dependent increased rate of NMSC was observed with UPA in RA. Trial Registration ClinicaTrials.gov identifier: NCT02706873, NCT02675426, NCT02629159, NCT02706951, NCT02706847, NCT03086343, NCT03104400, NCT03104374, NCT03178487, and NCT04169373.